Aggression and delinquent behavior in a large representative sample of high school students: Cannabis use and victimization as key discriminating factors. (February 2021) - Dugré, Jules R.; Potvin, Stéphane; Dellazizzo, Laura; Dumais, Alexandre
Highlights: Adolescents exhibiting distinct patterns of conduct problems may be differentiated from one another based on specific risk factors. This study used a two-step method to identify patterns of conduct problems and classify youths based on several risk factors associated with such problems. Cannabis use, victimization and hyperactivity were the best factors that discriminated between youths' membership to differential patterns of conduct problems. The results of this study may help to better identify youths at risk of disruptive behavior to implement preventative strategies. Abstract: Purpose: Since conduct problems (CP) vary distinctly across youths, better subtyping CP may be an important vehicle to study specific risk factors associated to differential patterns of CP. In a sample of 63, 196 adolescents, we employed a two-step method to the identify such CP patterns and to help classify youths based on several sociodemographic and psychopathological risk factors associated with CP. Methods: K-means clustering methods were first used to reduce the heterogeneity of CP by analyzing patterns of aggressive (AGG) and rule-breaking (RB) behaviors. A multi-class Classification and Regression Tree approach was further employed to examine the hierarchical interactions between risk factors specific to the emergence of different CP patterns. Results: Results revealed a three-cluster solution: (i) Low AGG-RB, (ii) High AGG and low RB, and (iii) High AGG-RB. The frequency of cannabis use, level of victimization and hyperactivity symptoms were the three factors best discriminating youths' membership to distinct patterns of CP. The model displayed a moderate to strong discriminatory capacity. Conclusion: Although this study provides evidence of key factors that may increase the risk of youths following specific patterns of disruptive behavior, additional research is necessary to clarify the etiology, longitudinal trajectories and outcomes related to these patterns.